Abnormal Connectivity and Brain Structure in Patients With Visual Snow - Aldusary, Njoud; Traber, Ghislaine L.; Freund, Patrick; Fierz, Fabienne C.; Weber, Konrad P.; Baeshen, Arwa; Alghamdi, Jamaan; Saliju, Bujar; Pazahr, Shila; Mazloum, Reza; Alshehri, Fahad; Landau, Klara; et al. (Frontiers in Human Neuroscience, 2020)
Objective. Visual snow (VS) is a distressing, life-impacting condition with persistent visual phenomena. Visual snow patients show cerebral hypermetabolism within the visual cortex, resulting in altered neuronal excitability. We hypothesized to see disease-dependent alterations in functional connectivity and grey matter volume in regions associated with visual perception. Methods. 19 patients with VS and 16 sex and age-matched controls were recruited. Functional magnetic resonance imaging (fMRI) was applied to examine resting-state functional connectivity (rsFC). Volume changes were assessed by means of voxel-based morphometry. Finally, we assessed associations between MRI indices and clinical parameters. Results. Patients with VS showed hyperconnectivity between extrastriate visual and inferior temporal brain regions and also between prefrontal and parietal (angular cortex) brain regions (p < 0.05, corrected for age and migraine occurrence). In addition, patients showed increased grey matter volume in the right lingual gyrus (p < 0.05 corrected). Symptom duration positively correlated to grey matter volume in both lingual gyri (p < 0.01 corrected). Conclusion. This study found VS to be associated with both functional and structural changes in the early and higher visual cortex, as well as the temporal cortex. These brain regions are involved in visual processing, memory, spatial attention, and cognitive control. We conclude that VS is not just confined to the visual system and that both functional and structural changes arise in VS patients, be it as an epiphenomenon or a direct contributor to the pathomechanism of VS. These in-vivo neuroimaging biomarkers may hold potential as objective outcome measures of this so far purely subjective condition.